STUDI ASOSIASI FUNGI MIKORIZA ARBUSKULA (FMA) PADA TEGAKAN EUCALYPTUS (Eucalyptus pellita) DI LAHAN GAMBUT - Pironi Ginanda Putra; Abdurrani Muin; Fathul Yusro (Universitas Tanjungpura, 2012)
Some of peatland in west borneo has been used for development of Industrial Plants Forests (IPF). One of those plants is Eucalyptus pellita. Aim of this research is determine the AMF (Arbuscular Mycorrhizal Fungi) association on E. pellita plants in the peatland area of PT. Kalimantan Subur Permai. Method of the research is spores isolation through wet process screening in gradually, coloring root, characteristics of spores in genus level and calculate the percentage of root infection.The result research show 6 species founded of AMF spores from one genus of Glomus and average percentage of root infection is 20% 36%. Keyword : association, arbuscular mycorrhizal fungi, E. pellita, peatland